(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Medical advances in the field of transplant immunology, surgical management and techniques of organ preservation have made the transplantation of human organs a viable approach for the treatment of end stage organ diseases. When vital organs like heart, lungs, liver, pancreas etc. suffer a functional damage that cannot be repaired by drugs or any kind of conventional surgical treatment, organ transplant is often the only solution to the problem. Procurement of human organs, however, has been the biggest challenge to the success of transplant programme in the country. Although the removal of human organs for therapeutic purposes has been legalized by the government, it has not yet received social sanction to facilitate cadaver transplant in our country. Professionally qualified social workers play a crucial role in procurement of human organs for transplantation. They coordinate the entire process of cadaver organ donation, undertake public education and awareness activities provide training and continuing education to hospital staff and carry out research studies on topics related to organ donation and transplantation. The paper discusses about the role and activities of the social worker in cadaver organ donation and transplantation coordination at a tertiary healthcare institute of the country.Organ donation is a noble act and it gives the opportunity to save the life of others even after death. Even with the technological improvement and man power resources, there is a huge need for human organs for transplantation. There are lots of hurdles in carrying out the process of organ transplantation due to misconceptions and lack of awareness. To improve organ donation lawfully, the essential factors are creating awareness, clarifying myths and misconceptions, educating legal procedures and eliminating malpractices like organ trade. In all these areas, social workers have major role and this article focuses on procedures of organ transplant and specific roles of social workers in the field of Organ Transplantation.